Analyses of the Dmrt family in a decapod crab, Eriocheir sinensis uncover new facets on the evolution of DM domain genes - Zhang, Peng; Yang, Yanan; Xu, Yuanfeng; Cui, Zhaoxia (Frontiers in Physiology, 2023)
DM domain genes are a group of transcription factors that are integral to sexual development and its evolution in metazoans. Their functions and regulatory mechanisms are not well understood in Malacostraca (crabs and crayfish) while these sex regulators have been widely identified in the past decade. In this study, the Dmrt family was investigated in the decapod crab, Eriocheir sinensis. We find that most members of the EsDmrt family begin to enrich around the juvenile 1 stage. In reproductive organs, EsDsx1, EsDsx2, EsiDMY and EsiDmrt1a highly express in the male-specific androgenic gland (AG), while EsDmrt-like, EsDsx-like, EsDmrt11E, and EsiDmrt1b show relatively high expression in testis. Also, we find the highly aberrant expression of EsiDMY and EsiDmrt1a in the chimeric AG, strongly indicating their function in AG development. Moreover, RNA interference of EsDsx1, EsiDMY, and EsiDmrt1a results in a significant decrease in transcription of the Insulin-like androgenic hormone (IAG), respectively. Our findings suggest that Dmrt genes in E. sinensis primarily function in male sexual differentiation, especially in AG development. Besides, this study identifies two unique groups of Dmrt genes in Malacostraca: Dsx and iDmrt1. In Malacostraca Dsx, we uncover a cryptic mutation in the eight zinc motif-specific residues, which were firmly believed to be invariant across the Dmrt family. This mutation sets the Malacostraca Dsx apart from all the other Dmrt genes and implies a different way of transcriptional regulation. Genes from the iDmrt1 group show phylogenetical limitation to the malacostracan species and underwent positive selection, suggesting their highly specialized gene function to this class. Based on these findings, we propose that Dsx and iDmrt1 in Malacostraca have developed unique transcriptional regulation mechanisms to facilitate AG development. We hope that this study would contribute to our understandings of sexual development in Malacostraca and provide new insights into the evolutionary history of the Dmrt family.